2012
DOI: 10.1074/jbc.m112.406512
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitivity of Kinase Activation by Blue Light Involves the Lifetime of a Cysteinyl-Flavin Adduct Intermediate, S390, in the Photoreaction Cycle of the LOV2 Domain in Phototropin, a Plant Blue Light Receptor

Abstract: Background:The plant photoreceptor "phototropin" is a light-regulated kinase containing the LOV photosensory domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
51
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 44 publications
4
51
0
Order By: Relevance
“…Upon return to the dark, the adduct state spontaneously decays to an oxidized flavin (LOV 450 ) on a timescale of seconds to days (17,18). Currently the biological role of the wide range in photocycle lifetimes is unknown; however, several studies have suggested that the range facilitates adaptation to changing levels of light intensity (17,19,20). For these reasons, chemical tuning of the LOV photocycle lifetime through understanding of the adduct decay mechanism has been attempted in several systems (2,17,18,(21)(22)(23)(24).…”
Section: Light-oxygen-voltage (Lov)mentioning
confidence: 99%
“…Upon return to the dark, the adduct state spontaneously decays to an oxidized flavin (LOV 450 ) on a timescale of seconds to days (17,18). Currently the biological role of the wide range in photocycle lifetimes is unknown; however, several studies have suggested that the range facilitates adaptation to changing levels of light intensity (17,19,20). For these reasons, chemical tuning of the LOV photocycle lifetime through understanding of the adduct decay mechanism has been attempted in several systems (2,17,18,(21)(22)(23)(24).…”
Section: Light-oxygen-voltage (Lov)mentioning
confidence: 99%
“…Within seconds to minutes, the S390 reverts to D450, thermally depending on the types of LOV (14), and forms a characteristic photocycle with LOV. S390 is a signaling state capable of activating the kinase (15). Of the two LOV domains, LOV2 has been shown to play a major role in kinase activation by BL through both autophosphorylation (16,17) and substrate phosphorylation in vitro (18).…”
mentioning
confidence: 99%
“…One of the main reasons for this problem is the difficulty in preparing phot samples consisting of both LOV and KD with a high enough purity and in large enough quantities for biophysical analyses. To overcome this difficulty, we previously established a preparation system for pure LOV2-KD of At phot1 and phot2 (15,26). The LOV2-KDs showed BL-regulated kinase activity on the N-terminal fragment of At phot1 (AtP1Nt), including the autophosphorylation sites around the LOV1 region that was created as an artificial substrate for the phot kinase (15,26).…”
mentioning
confidence: 99%
See 2 more Smart Citations